Forgotten people : poverty, risk and social security in Indonesia : the case of the Madurese - Nooteboom, Gerben, 1970- (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2015)
"Forgotten People deals with people living at the fringes of the Indonesian society. It describes and analyses their livelihoods and styles of making a living from an insider perspective. While Indonesia has experienced steady economic growth for more than a decade, the livelihoods and lifestyles of poor people and migrants confronted with poverty and insecurity have received less attention. This book describes and analyses diversity in livelihood strategies, risk-taking and local forms of social security (social welfare) of people living below or close to the Indonesian poverty line. It puts two categories of forgotten people at the centre. Peasants, living in remote areas in rural Java, and Madurese migrants craving for a better life in urban and rural East Kalimantan"-- Provided by publisher.